(untitled) (Interdisciplinary Studies Journal, 2025)
This study presents contemporary Indigenous Brazilian literature as a cultural expression and a political resistance tool for native peoples. The objective is to highlight the role of this literary production in preserving Indigenous identities and promoting intercultural dialogue. The adopted methodology is a qualitative approach based on bibliographic review and academic studies. The research addresses the historical trajectory of Indigenous literature, the relationship between orality and writing, and the challenges faced regarding its insertion in the publishing market and the educational system. The results show that Indigenous literature contributes to deconstructing stereotypes, strengthening collective memory, and increasing the visibility of Indigenous cultures. It is concluded that recognizing this literary production is essential for building a more just and plural society capable of valuing Brazil’s cultural diversity.